Walter Benja-Memes. Issue 2 (3rd July 2019) - Hardesty, Robby; Linz, Jess; Secor, Anna J.
Abstract : This paper aims to unlock the potential for the politicization of art in the age of the meme. Drawing on Walter Benjamin's ideas, we suggest that technologies of viral reproduction create the tools and conditions for blasting the present moment out of the oppressive vice of classical historiography. While fascism retrenches on "art for art's sake" in defense of principles of origin, authenticity, and mastery, we envision a politicization of the art of the meme not simply through content but through practice. This paper attempts to engage in this practice through creative invention. We work across two cases, one "real" (Richard Spencer gets punched) and one of our own creation: the viral life and death of Quodlibet, an anachronistic DJ. Our wager is that the blast of now-time that the meme unleashes can be used to lay bare the myth of mastery and open a space for new subjects, forms, and practices. At the same time, we show how the meme is prone to boomerang effects and reterritorializations that can reverse back into fascist aestheticism, the catastrophic status quo, and the dominance of the market. Playfully and without self-seriousness, our goal in this paper is to open the image sphere: to slip into the Internet's dream house and rummage its drawers for a revolutionary politics.